Arbuscular Mycorrhizal Fungi (Rhizophagus clarus) and Rhizobacteria (Bacillus subtilis) Can Improve the Clonal Propagation and Development of Teak for Commercial Plantings - Alexandre, Flávia Sampaio; Della Flora, Larissa Venturini; Henrique, Ivanildo Guilherme; da Silva, Daniely Camila; Mercedes, Andreza Pereira; Cardoso Silva, Aline; Silva de Oliveira, Afonso; Bondespacho da Silva, Mariane Patrícia; Formelh Ronning, Bruna Patrícia; Dreher, Douglas Rafael; Gionco Cano, Bárbara; Andreata, Matheus Felipe de Lima; et al. (Frontiers in Plant Science, 2021)
The Tectona grandis L. f. (Teak) is an important forest species with high economy value in Asia, Africa and Latin America. In Latin America, Brazil is one of the countries with the most cultivated areas. The cultivation of Teak turns out to be challenging due to its high nutritional demand and the need for seedling production by clonal propagation that includes about 90 days in the nursery phase. The optimization of seedling production is necessary for better results in the nursery and to enhance growth in the field. In this way, the well-known advantage of using microorganisms that promote plant development appears as a potential biotechnological approach to be explored and for the implantation of new areas of wood production. In this work, the inoculation of Bacillus subtilis, as plant growth-promoting rhizobacteria (PGPR) was evaluated, Rhizophagus clarus (an arbuscular mycorrhizal fungus - AMF) and the co-inoculation of these microorganisms in the Teak seedling production phase can improve the development of commercial plantations in field conditions. Experiments were carried out under greenhouse and field conditions to evaluate four treatments based on substrate inoculation of the seedlings. Treatments consisted of a non-inoculated control, PGPR inoculation, AMF inoculation and PGPR + AMF inoculation. The results of the biometric evaluation of seedlings at the greenhouse showed that there was significant difference of AMF inoculation and PGPR + AMF inoculation in terms of the specific root length and the root density treatments, there was also a positive correlation between these two treatments and the absorption of some nutrients such as P, N, K, Mg, Cu, Mn and Zn. This response led an increase between 4.75% to 11.04% in the growth rate in field.